2012
DOI: 10.5796/electrochemistry.80.834
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Evolution and Reduction Reactions on La0.8Sr0.2CoO3 (001), (110), and (111) Surfaces in an Alkaline Solution

Abstract: The oxygen evolution and reduction properties of La 0.8 Sr 0.2 CoO 3 are characterized using two-dimensional model electrodes with different reaction planes, synthesized on SrTiO 3 single crystal substrates by pulsed laser deposition. Thin-film X-ray diffraction and reflectivity measurements confirm the epitaxial growth of 29-nm-thick La 0.8 Sr 0.2 CoO 3 (001), (110), and (111) films on SrTiO 3 (001), (110), and (111) substrates, respectively. Cyclic voltammetry curves in 1-M KOH aqueous solution indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 17 publications
4
33
0
Order By: Relevance
“…All Mn-containing perovskites showed catalytic activity but the weak dependence on rotational speed in RDE measurements [127,128] suggests that oxygen is not directly reduced to water on these surfaces, which is in agreement with microkinetic analysis of composite electrodes [97]. LaCoO 3 [60,129] [96,131] showed no activity but could be activated by addition of carbon [96]. Due to the similarity in the chemistry of the Co-based perovskites, the discrepancy is unlikely to be caused by doping of divalent cations and requires further studies.…”
Section: Activity Metricssupporting
confidence: 78%
See 1 more Smart Citation
“…All Mn-containing perovskites showed catalytic activity but the weak dependence on rotational speed in RDE measurements [127,128] suggests that oxygen is not directly reduced to water on these surfaces, which is in agreement with microkinetic analysis of composite electrodes [97]. LaCoO 3 [60,129] [96,131] showed no activity but could be activated by addition of carbon [96]. Due to the similarity in the chemistry of the Co-based perovskites, the discrepancy is unlikely to be caused by doping of divalent cations and requires further studies.…”
Section: Activity Metricssupporting
confidence: 78%
“…However, the chemical, structural, and magnetic properties of the oxides are likely not fully optimized as will be argued in Section 6. In contrast to single crystalline Pt (Figure 3a), the activity of single crystalline perovskite oxides depends weakly on the surface facet (Table 2) in previous reports [63,96,131], so that the most commonly investigated (100) surfaces are compared. The most active composite electrodes [22] are also included for reference.…”
Section: Activity Metricsmentioning
confidence: 99%
“…Recently, some studies have shown that carbonaceous materials can make electrocatalytic contributions to the ORR in alkaline solutions . In addition, the intrinsic catalytic properties of perovskites themselves were studied by using stationary electrodes of perovskites fabricated by pulsed laser deposition (PLD) . Our group reported, for the first time, the intrinsic electrochemical properties of perovskites as an oxygen electrode through the combined use of PLD‐grown perovskite thin films and rotating disk electrodes (RDEs) : Even La 0.8 Sr 0.2 CoO 3 (LSCO), which is known to be a highly electroconductive perovskite, showed much lower ORR activities than those of the composite electrodes, whereas LSCO exhibited clear OER activities that were as high as those of the composite electrodes.…”
Section: Figurementioning
confidence: 99%
“…[171][172][173][174][175][176][177] Ir x Ru y Ta z O 2 as an anode electrocatalyst achieved an overall cell voltage of 1.57 V at 1 A cm −2 at 80 °C, with an energy consumption of 3.75 kWh N m −3 H 2 and efficiency of 94%, for a total noble metal loading of less than 2.04 mg cm −2 . 47 However, there are some non-noble, less expensive metals that also present electrocatalytic activity and are being introduced for use in oxygen [178][179][180][181][182][183][184][185] and hydrogen 165,166,[186][187][188][189][190][191] evolution reactions. Additionally, during designing an electrode, it is normally doped or coated with more stable and active layers.…”
Section: Future Trendsmentioning
confidence: 99%